Heterogeneous small-scale forest ownership: complexity of management and conflicts of interest - Peter Kumer; Irma Potočnik Slavič (Belgeo)
Forest landscape in Slovenia is large and fragmented. The majority of owners (489,000) own only small forest land (less than 5 hectares), which is a result of intensive societal, political and economic changes that have occurred over the last two centuries. Land reforms, old-field succession, impartial inheritance and restitution after 1991 are the main factors that have produced a large number of owners. Since they mainly inherited the forest, they constitute a very broad and heterogeneous group. The small-scale owners, as a specific social group, lack the knowledge, skills and capacity for efficient forest management. They have changed their attitude toward their forest in recent decades and have mostly shifted from production to multi-objective orientation. A three-step approach for theoretical sampling was used to collect variety of qualitative data suitable for Glaser’s (1998) variation of grounded theory. The theory has emerged around three core categories: (1) land fragmentation and co-ownership and (2) demographics and (3) remoteness. We found that land fragmentation builds suspicion and distrust between owners and their willingness to cooperate. The disappearing group of residential owners, often affiliated with agriculture, holds emotional interest to manage the forest although income generation is insignificant. Remote owners are disassociated with their forest and carry almost no forestry activities.